Impact of Intercollegiate Athletics on Undergraduate Enrollment at a Small, Faith-Based Institution - Matthew J. Brunet; Michele W. Atkins; Gary R. Johnson; Linn M. Stranak (Journal of Applied Sports Management, 2013)
Based on previous research, it is apparent many National Collegiate Athletic Association (NCAA) Division I institutions benefit from the existence of and success in intercollegiate athletics. However, few studies have researched the impact of intercollegiate athletics at National Association of Intercollegiate Athletics (NAIA) institutions. Therefore, the purpose of this study was to investigate the effect of intercollegiate athletics at a small, faith-based institution affiliated with the NAIA. More specifically, does success in or the existence of intercollegiate athletics have an effect on students’ decisions to enroll at this institution? Findings indicate the majority of freshmen student participants, including many intercollegiate athletes, were not considerably influenced by the existence of intercollegiate athletics or the existence of successful intercollegiate athletics when deciding to attend the institution. These findings indicate the need for similar institutions to reevaluate the importance placed on and benefits derived from intercollegiate athletics.
Keywords: Athletics; enrollment; NAIA; NCAA; college